The Role Of rs1799883 Polymorphism Of The FABP2 Gene In The Pathogenesis Of Nosological Syntropy Of Gallstone Disease And Metabolic Syndrome - Pulatboevich, Raximov Anvar; Safaevich, Ismailov O’ktam; Yusupovich, Batirov Davronbek (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
Objective: to study the role of the rs1799883 polymorphism of the FABP2 gene in the pathogenesis of gallstone disease in combination with MS. Material and methods. Molecular genetic studies were carried out in the Department of Molecular Medicine and Cell Technologies of the RSNPMC Hematology. The analysis of the associations of the rs1799883 polymorphisms of the FABP2 gene was carried out using a case-control model. The main group consisted of 118 patients with cholelithiasis in combination with MS living in the Khorezm region. Results: As a result of our research, we identified a significant association of the homozygous genotype for the Thr allele with the development of gallstone disease in combination with MS. The indicator of the ratio of the chances of developing gallstone disease in combination with MS in carriers of this genotype was OR = 2.9 at 95% CI: 1.122- 7.424. The relative risk of disease was RR = 2.5 with 95% CI: 1.11-5.76. Conclusion: Our results allow us to conclude that the homozygous Thr/Thr genotype plays an important role in the formation of gallstone disease and obesity in people of Uzbek nationality.